Formability Characteristics of Industrial Pure Aluminum at Casting and Room Temperature - Karaaslan, Ahmet (WALTER DE GRUYTER GMBH, 2009)
In this work, changes in mechanical properties of aluminum after continuous casting has been studied. Molten aluminum (Al 1235) was converted directly into an endless coiled strip, suitable for cold rolling, using a twin drum continuous casting process. After hot forming, industrial pure aluminum Al 1235 was rolled at room temperature to different reduction ratios. Tensile strength, elongation, and Vickers hardness of the aluminum were determined experimentally. The theoretical part comprises also analytical modeling. The results revealed the formability characteristics of material depending on the process. The mechanical properties of the rolled sheets in the hot forming process are poorer than those in the cold rolled case.
Keywords: Materials Science